Analysis of a hybrid dry cooling system for solar thermal electricity plants in deserts. (5th March 2021) - Biencinto, Mario; Rojas, Esther; Bayón, Rocío
Highlights: Hybrid dry cooling with latent heat storage and air-cooled condenser is proposed. Intended for solar thermal electricity plants with low water availability. This concept improves power block efficiency and reduce parasitic consumptions. Seven desert locations, two PCMs and two operation strategies have been simulated. Up to 0.6% increase in net annual efficiency compared to conventional dry cooling. Abstract: This work analyses a new concept of hybrid dry cooling system composed of a latent heat storage module and an air-cooled condenser intended for solar thermal electricity plants located in desert locations with low water availability. This hybrid system is expected not only to improve the power block efficiency but also to reduce parasitic consumptions of air-cooled condensers, taking advantage of the temperature oscillations in such locations. For evaluating those advantages, a simulation model of a solar thermal plant that includes either conventional dry or hybrid cooling system has been developed with TRNSYS, so that both approaches can be compared. The annual behaviour of the corresponding plants in terms of electricity production has been simulated for various desert locations, different cooling system configurations and two phase change materials (PCM) for the latent module: RT35HC and Paraffin C21, with melting temperatures of 35 °C and 40 °C, respectively. Also, suitable operation strategies have been evaluated in order to optimize the performance of the hybrid cooling concept. Simulation results show that an increase in net electricity from 0.3% to 0.6% for Paraffin C21 or from 0.1% to 0.5% for RT35HC could be obtained per year if a hybrid cooling system is used. The use of a PCM with higher melting points such as Paraffin C21 seems to provide better results in terms of net annual production, particularly in locations with high ambient temperatures at night (like Abu Dhabi or Aswan). Although issues like electricity prices, financial and equipment costs should also be considered, a preliminary economic analysis shows that the cost-to-latent heat ratio of the PCM should be below 4.5 ∙ 10 -3  €/kJ to enable the feasibility of the proposed concept.